2009
DOI: 10.1021/nn901239z
|View full text |Cite
|
Sign up to set email alerts
|

Transparent Conductive Coatings by Printing Coffee Ring Arrays Obtained at Room Temperature

Abstract: We report here a concept for utilization of the "coffee ring effect" and inkjet printing to obtain transparent conductive patterns, which can replace the widely used transparent conductive oxides, such as ITO. The transparent conductive coating is achieved by forming a 2-D array of interconnected metallic rings. The rim of the individual rings is less than 10 microm in width and less than 300 nm in height, surrounding a "hole" with a diameter of about 150 microm; therefore the whole array of the interconnected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
263
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(269 citation statements)
references
References 15 publications
4
263
0
2
Order By: Relevance
“…At the same timeit was found that the silver NMS's with sizes from 0.5 to 20 nm are uniformly distributed on the substrate surface that is consistent with the ideas of the "coffee stains" model [8] [9] [10].…”
Section: Silver Nano-/microstructures Deposited From Fogsupporting
confidence: 64%
See 3 more Smart Citations
“…At the same timeit was found that the silver NMS's with sizes from 0.5 to 20 nm are uniformly distributed on the substrate surface that is consistent with the ideas of the "coffee stains" model [8] [9] [10].…”
Section: Silver Nano-/microstructures Deposited From Fogsupporting
confidence: 64%
“…A promising approach to solve this problem may be thecreation of the metallic NMS precipitates formed during the evaporation of the micro-droplets from the metallic NMP colloidal solutions in various solvents [8] [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One consists of the formation of transparent conductive grid patterns by self-assembly of Ag nanoparticles deposited by ink-jet printing. [96] Another approach, closer to the standard one using macroscopic metal Conductivity in relation to synthesis temperature (or annealing temperature) for selected transparent n-type and p-type conductors reported in literature. The color bar represents the absorption coefficient (averaged from 400-700 nm), with white the lowest (most transparent) and blue the highest (least transparent).…”
Section: Metal Nanowires Nano-and Microgrids and Ultrathin Filmsmentioning
confidence: 99%